Women and citizenship in Britain and Ireland in the twentieth century : what difference did the vote make? - Thane, Pat; Breitenbach, Esther (Continuum, 2010)
The continuing under-representation of women in political and public life remains a matter of concern across a wide range of countries, including the UK and Ireland. A collection of scholars explore key questions in the development of women's rights in Britain and Ireland.